VALIDATION OF UV-SPECTROMETRY ASSAY METHOD FOR DISSOLUTION PROFILE TEST FOR MOXIFLOXACINE TABLETS - L. A. Menshikova; A. A. Lvova; I. E. Shohin; Yu. E. Boldina; T. N. Komarov; Yu. V. Medvedev (Разработка и регистрация лекарственных средств)
Validation of UV-spectrometry assay method for dissolution profile test for levofloxacine tablets was carried out. The evaluated validation characteristics were: specificity, linearity, accuracy, precision, and analytical range. It was shown than main validation characteristics meet the Russian State Pharmacopoeia XIII requirements.